Association between gender and the nutritional status of school-age children with food acceptance (Revista Contexto & Saúde, 2023)
The objective of the research was to evaluate the association of sex and nutritional status of schoolchildren with food acceptance. 626 students, aged between 7 and 10 years, from Guarapuava, PR, participated. Nutritional assessment was performed based on the Body Mass Index for age and sex. Although most children present a normal nutritional status (58.31%), a high number of students presented weight above the ideal (40.73%). Girls were more associated with the cereals, fruits, vegetables and dairy groups. Boys, on the other hand, are more associated with foods belonging to the groups of meat and eggs and oils and fats, similarly to what was observed for eutrophic children. Overweight children were less associated with these food groups. It is concluded that sex and nutritional status of school-age children are associated with food acceptance.
Keywords: Feeding; Consumption; Child; School